Development of Cyclodextrin-Functionalized Transethoniosomes of 6-Gingerol: Statistical Optimization, In Vitro Characterization and Assessment of Cytotoxic and Anti-Inflammatory Effects - Eman A. Mazyed; Farid A. Badria; Mai H. ElNaggar; Soha M. El-Masry; Sally A. Helmy (MDPI AG, 2022)
The poor solubility and stability of 6-gingerol (6-G) could hamper its clinical applications. The aim of the current study was to develop a novel ultra-deformable cyclodextrin-functionalized transethoniosomes (CD-TENs) as a promising delivery system for 6-G. Transethoniosomes (TENs) are flexible niosomes (NVs) due to their content of ethanol and edge activators (EAs). CD-functionalized nanoparticles could improve drug solubility and stability compared to the corresponding nanovesicles. 6-G-loaded ethoniosomes (ENs) were formulated by the ethanol injection technique in the presence and absence of EA and CD to explore the impact of the studied independent variables on entrapment efficiency (EE%) and % 6-G released after 24 h (Q24h). According to the desirability criteria, F8 (CD-functionalized transethoniosomal formula) was selected as the optimized formulation. F8 demonstrated higher EE%, permeation, deformability and stability than the corresponding TENs, ENs and NVs. Additionally, F8 showed higher cytotoxic and anti-inflammatory activity than pure 6-G. The synergism between complexation with CD and novel ultra-deformable nanovesicles (TENs) in the form of CD-TENs can be a promising drug delivery carrier for 6-G.